Comparison of Mastectomy and Thyroidectomy Techniques in Modern Oncological Surgical Practice: A Systematic Review and Analysis of Results - Rudi Haris Munandar (International Journal Labs, 2025)
Mastectomy and thyroidectomy are the main surgical procedures in the treatment of breast and thyroid cancer. As technology develops, these two procedures undergo significant transformations through minimally invasive, endoscopic, and robotic techniques. The study aimed to compare modern techniques in mastectomy and thyroidectomy based on clinical outcomes, complications, surgery time, and patient satisfaction levels. This study uses a systematic review method of scientific literature published between 2020–2024. The results showed that minimally invasive techniques in both procedures provided better aesthetic results, faster recovery, and lower complications than conventional techniques.